Tourism business management in the aspect of earnings management by travel agencies in times disease threats – evidence from Poland - Franczak, Iwona; Bakota, Daniel (Journal of Business Economics and Management, 2024)
This study examines the existence of earnings management by travel agencies operating in Poland at the time of global disease threats over the last decade. To measure earnings management the estimation of total discretionary accruals was used constituting some changes in the working capital. Among the available research methods, hypothesis verification procedures based on panel models have been selected. It is found, that in the times of economic prosperity, the phenomenon of earnings management does not occur as it is not necessary. In tough years, when the actual financial result becomes unsatisfactory, shaping the result is used as a tool for its correction. Interpretation of the results requires caution due to their sensitivity to the adopted research methodology. They should be treated as an incentive to a thorough analysis of the content of financial statements and to research into the earnings management of tourism businesses.